«LEDA AND THE SWAN» BY S.D. ERZIA (1922, 1929) IN THE CONTEXT OF ARTISTIC TRADITION - Irina V. Klyueva (Russian Studies in Culture and Society)
The purpose of this study is to identify the peculiarities of the interpretation of the ancient myth of Leda and the Swan in the work of sculptor Stepan Dmitrievich Erzia (1876–1959), twice addressing this topic – in 1922 in the Caucasus (Caucasian walnut wood) and in 1929 in Argentina (quebracho). To achieve this goal, the methodology of culturology and art history was used: comparative historical method; iconographic method, as well as formal-stylistic analysis of works of sculpture, including their interpretation (symbols and meaning) and stylistic definition. The sources of the research are the original works on this topic created by the sculptor and now located in the Mordovia Republican Fine Arts Museum named after S.D. Erzia; materials from the Russian and foreign press of the 1920s, containing reviews of the sculptor’s works. It is shown that, being in the field of attraction of the Art Nouveau style and symbolism, which had a special attraction to the theme of “Leda and the Swan”, in its interpretation the artist gravitated towards individual solutions and iconographic non-standardism.